Health effects associated with chewing tobacco: a Burden of Proof study - Gabriela F. Gil; Jason A. Anderson; Aleksandr Aravkin; Kayleigh Bhangdia; Sinclair Carr; Xiaochen Dai; Luisa S. Flor; Simon I. Hay; Matthew J. Malloy; Susan A. McLaughlin; Erin C. Mullany; Christopher J. L. Murray; et al. (Nature Communications, 2024)
Abstract Chewing tobacco use poses serious health risks; yet it has not received as much attention as other tobacco-related products. This study synthesizes existing evidence regarding the health impacts of chewing tobacco while accounting for various sources of uncertainty. We conducted a systematic review and meta-analysis of chewing tobacco and seven health outcomes, drawing on 103 studies published from 1970 to 2023. We use a Burden of Proof meta-analysis to generate conservative risk estimates and find weak-to-moderate evidence that tobacco chewers have an increased risk of stroke, lip and oral cavity cancer, esophageal cancer, nasopharynx cancer, other pharynx cancer, and laryngeal cancer. We additionally find insufficient evidence of an association between chewing tobacco and ischemic heart disease. Our findings highlight a need for policy makers, researchers, and communities at risk to devote greater attention to chewing tobacco by both advancing tobacco control efforts and investing in strengthening the existing evidence base.